DSM-5 Changes in Attention Deficit Hyperactivity Disorder and Autism Spectrum Disorder: Implications for Comorbid Sleep Issues - Ujjwal P. Ramtekkar (MDPI AG, 2017)
Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorder (ASD) are the most common neurodevelopmental disorders. Despite significant comorbidity, the previous diagnostic criteria prohibited the simultaneous diagnosis of both disorders. Sleep problems are highly prevalent in both disorders; however, these have been studied independently for ADHD and ASD. In the context of revised criteria in the Diagnostic Statistical Manual of Mental Disorders 5th edition (DSM-5) that allows combined diagnosis of ADHD and ASD, this short review presents an overview of relationship between sleep problems, ADHD and ASD, as well as conceptualizing the shared pathophysiology. The practical considerations for clinical management of sleep problems in combination with ADHD and ASD are also discussed.